Analiza i ocena skuteczności oraz efektywności zarządzania projektem współfinansowanym ze środków unijnych w przedsiębiorstwach dolnośląskich - Krzos, Grzegorz (Analysis and Effectiveness Assessment of Project Management Co-Financed by UE Funds Implemented in Lower Silesian Enterprises, 2006)
The main goal of this article is to present results of the pilot research work in 113 Lower Silesian enterprises on the scale of the project management method being used in the process of funds absorption for company development from the European Union. One of the goals in this research work was assessment of effectiveness of obtaining EU grants by SME in the years 2004 and 2005. In the research much attention was paid to the way the enterprises use the methodology and instruments of project management in the process of obtaining grants.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 438-448